Quantifying the link between heavy precipitation and Northern Hemisphere blocking—A Lagrangian analysis - Lenggenhager, Sina; Martius, Olivia (Atmospheric Science Letters, 2020)
Atmospheric blocks strongly influence surface weather, including extremes such as heat waves and cold spells. Recently, diabatic heating and associated upper‐tropospheric potential vorticity (PV) modification have been identified as important modulators of atmospheric blocking dynamics. Also, robust links between atmospheric blocks and proximate heavy precipitation events have been established. This leads to the question of the extent to which diabatic heating associated with heavy precipitation events influences Northern Hemisphere blocking. This study uses 5 years of 3‐day back trajectories started from objectively identified blocks in the ERA‐Interim dataset to investigate this relationship. A substantial fraction of air parcels in blocks pass through heavy precipitation areas. The exact fraction depends on the choice of heavy precipitation threshold. Roughly 19% of all the trajectories in a block pass a heavy precipitation area (>95th percentile) area while being saturated. Of the air parcels in a block that are heated at least 5 K, 60% pass a heavy precipitation area while saturated. This fraction varies with the season and geographical area. The overall fraction is lowest in summer and highest in winter, higher over oceans than over land, and higher over the Pacific than over the Atlantic. In summer, heating is relevant over the continents and heating over North America influences blocks over the eastern Atlantic. For summer blocks in the North Atlantic and over Scandinavia, heating happens partly over the European continent.